2009
DOI: 10.1007/s11172-009-0127-y
|View full text |Cite
|
Sign up to set email alerts
|

Benzoaza-15-crown-5 ethers: synthesis, structure, and complex formation with metal and ethylammonium ions

Abstract: Benzoaza 15 crown 5 ethers containing one or two nitrogen atoms in different positions of the macrocycle and bearing different substituents at these atoms were synthesized. The structures of azacrown ethers and their metal complexes were studied by X ray diffraction. The stability constants of the complexes of azacrown ethers with Na + , Ca 2+ , Ba 2+ , Ag + , Pb 2+ , and EtNH 3 + ions were determined by 1 H NMR titration in MeCN d 3 . In free benzoazacrown ethers containing secondary nitrogen atoms bound to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…NMR studies. Earlier, 4, 13 we have demonstrated that benzomonoazacrown ethers and their derivatives contain ing the tertiary N atom conjugated with the benzene ring form sufficiently stable guest-host complexes with alkali, alkaline earth, heavy metal, and ammonium ions, which will make them highly efficient as ionophores in promis ing optical chemosensory compounds. It was interesting to compare the quantitative stability parameters of com plexes of nitrobenzoazacrown ethers with Groups I and II metal cations and ammonium ions, to reveal the structur al features of the resulting complexes and their selectivity toward various ions, and to compare the complexing ability of nitrobenzoazacrown ethers containing various N alkyl substituents with that of related compounds.…”
Section: Resultsmentioning
confidence: 91%
See 3 more Smart Citations
“…NMR studies. Earlier, 4, 13 we have demonstrated that benzomonoazacrown ethers and their derivatives contain ing the tertiary N atom conjugated with the benzene ring form sufficiently stable guest-host complexes with alkali, alkaline earth, heavy metal, and ammonium ions, which will make them highly efficient as ionophores in promis ing optical chemosensory compounds. It was interesting to compare the quantitative stability parameters of com plexes of nitrobenzoazacrown ethers with Groups I and II metal cations and ammonium ions, to reveal the structur al features of the resulting complexes and their selectivity toward various ions, and to compare the complexing ability of nitrobenzoazacrown ethers containing various N alkyl substituents with that of related compounds.…”
Section: Resultsmentioning
confidence: 91%
“…In this respect, nitro derivatives 1 differ from benzene unsubstituted benzoazacrown ethers and their formyl derivatives: their complexes with the cat ions in question are much more stable than similar com plexes of related N phenylaza 15 crown 5. 13 This be havior of compounds 1 can be explained by two factors: first, the coordination bond N...M + is weakened because of the strong electron withdrawing effect of the NO 2 group and, second, the substituent at the N atom presents steric hindrances to its coordination to the large Ba 2+ ion. The second reason is indirectly confirmed by the inability of crown ether 1c, which contains a bulky n propyl substitu ent, to form stable sandwich complexes.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Selected bond lengths (d), deviation of the metal cation from the middle plane passing through all heteroatoms of the macrocycle (ΔM m+ ), bond (ω) and torsion (ϕ) angles and the sum of the bond angles at the S atom (Σ ω ) in crown ethers 5, 6•3H 2 (1.386(2)-1.398(2) Å) as compared with the free ligand 5 is observed, which is typical of complexation of benzocrown ethers. 31 The values of the bond angles C Ar -C Ar -O(1) and C Ar -C Ar -S(1) in the complex do not virtually differ from the analogous parameters of the free ligand 5 (see Table 2) suggesting small changes in hydridization of the O and S atoms linked with the benzene ring. The sodium cation is coordinated to two oxygen atoms of the perchlorate anion and three oxygen atoms of macrocycle of 5 that are remote from the benzene ring (see Fig.…”
Section: Methodsmentioning
confidence: 88%